How Social Factors Shape the Mental Health Impact of Social Media Among High School Students: Systematic Literature Review - Handayani, Lina; Rizkiyah Assyukru, Faatih; Nisa Novianti, Tria (VISIKES, 2025)
Adolescent mental health has emerged as a pressing global concern, particularly in light of the growing and intensive use of social media among high school students. While social media platforms offer avenues for communication and self-expression, they also contribute to adverse psychological outcomes, including anxiety, stress, and depression. This study explores the role of social determinants—such as socioeconomic status, family dynamics, peer support, and digital literacy—in shaping the mental health effects of social media use among adolescents. Employing a literature review methodology, the study analyzed 25 relevant national and international journal articles sourced via Google Scholar using the keywords: “social determinants,” “social media,” “mental health,” and “adolescents.” The findings reveal a strong correlation between frequent social media engagement and heightened mental health disorders, exacerbated by contextual factors such as inadequate parental supervision, limited emotional support, and peer norms that prioritize online validation. These insights underscore the urgent need for integrated, cross-sectoral interventions involving families, schools, and community stakeholders. Strengthening adolescents’ psychosocial resilience through targeted digital literacy education and robust social support systems is essential to mitigate the negative impacts of social media and promote overall mental well-being.